Comparison of bioinspired algorithms applied to the timetabling problem in sport (2020)
The problems of timetabling tasks or events, in general, are subject to sets of restrictions such as: creation of work roles, operation of different teams, operation personnel, among others. These types of problems are classified as NP class [1]. In this study, special attention is paid to the scheduling problem applied to sports clubs, for which different bioinspired algorithms are implemented and compared.